Assessment of Sijil Simpanan Premium (Premium Saving Certificate) in Bank Simpanan Nasional from Shari'ah perspective - Razi Hassan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
This study aims to examine and evaluate the issues in Premium Savings Certificate from the Shari'ah viewpoint. This study is motivated by the fact that although there are already discussions on Premium Savings Certificate, they are not inclusive and only look into the situation at the time of its launch 30 years ago. The study focuses on explanation about operation methods of Premium Savings Certificate which covers various aspects especially related to issues of providing prizes, lucky draw methods in selecting winners, contract aspects, and investment funds made by Bank Simpanan Nasional. Evaluation and study carried out are based on Islamic mu 'amalah principles, Fiqh methods as well as Muslim jurists opinions by looking at the elements which are not compliant with Islamic rulings. The objective of this study is to ensure this product complies with the principles of the Shari'ah and at the same time re-branding it to be in line with the Fiqh perspective and Islamic Shari'ah. This is in view of this product possessing huge potential in generating funds as well as investments, hence forming a huge capital in the development of the Muslim economy. The results of the study found that there are matters which oppose the Islamic mu'amalah principles in Premium Savings Certificate and several recommendations have been forwarded such as the used of mudarabah contract and Shari'ah compliance investment may be applied to fulfill the requirement of the Islamic Shari'ah.